Algorithmic Replication of Macramé Techniques: Bridging Analog Movements With Computational Design - ÇEVİK, AYŞE NESLİGÜL; Açıkgöz, Ece Kumkale (Emerald Publishing, 2025)
PurposeThis study explores how traditional macram & eacute; techniques can be digitally controlled and automated, contributing to the preservation of cultural heritage and offering a new perspective for innovative architectural applications. By translating macram & eacute;'s knot-making process into a computational model, this research aims to protect traditional know-how and transfer it to future generations while addressing modern design challenges related to adaptive, sustainable building solutions.Design/methodology/approachThe research involves a review of literature on the geometric and mechanical analysis of macram & eacute; weaving, focusing on knot tightness, yarn thickness and the resulting structural rigidity, as well as their digital counterparts. By using Rhino/Grasshopper, the study develops an adaptable digital macram & eacute; model capable of mimicking analog knot-making movements. In addition, two parametric variations (tight vs. loose knots) were tested as daylight-control systems through digital simulation. Luminance data were analyzed using ImageJ, incorporating brightness histograms and false-color heatmaps to assess performance.FindingsThe study demonstrates that digital simulations of macram & eacute; movements can enhance both the precision of production and its adaptability to architectural applications such as shading and airflow modulation. The luminance analysis indicates a substantial variation in daylight performance based on knot tightness. However, the current parametric script is limited in its adaptability to 3D geometries due to coordinate system constraints, which are discussed as a key area for future development.Originality/valueThis research advances the field of digital-analog integration by developing an algorithm that not only replicates traditional macram & eacute; movements but also tests their performance in a building context. By digitally preserving cultural knowledge and applying it in adaptive fa & ccedil;ade systems, the study aligns with SDG 11 (Sustainable Cities and Communities) and SDG 9 (Industry, Innovation and Infrastructure), demonstrating how traditional crafts can inform sustainable and responsive architectural solutions.
Keywords: Algorithmic Design; Computational Design; Knot Theory; Macramé; Parametric Modeling; Sustainable Architecture; Textile Fabrication